Supporting Game Software Engineering from Business Modeling Towards Building Digital Game Studios - dos Santos, Rodrigo Pereira; Xavier, Bruno; Viana, Davi (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2024: Anais do XXIII Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames.2024.241002, 2024)
The growth of the network of actors and solutions in the market has created a scenario in which fast, frequent technological changes as well as high quality level of the products are of utmost importance, affecting game software engineering. In the scenario, digital games stand out for the remarkable presence of leading software distribution platforms while the emergence of platforms dedicated to digital games and the growing network of actors and solutions for specific domains is also a reality. Several difficulties regarding actors’ entrance and survival can be pointed out. As such, specific business models to assist in building digital game studios should be considered from the existing solutions reported in the game software engineering literature. This paper aims to report on the definitions and business modeling components applied to digital games research and practice to support game software engineering towards building digital game studios. We extracted data from 40 studies and categorize them into two related subdomains, i.e., definitions and components. Based on the results, we observe that such sector does not appropriate the definitions and components on business modeling, even though several studies mention related concepts. Therefore, this work reinforces the need for exploratory research, mainly empirical studies in real-life solutions throughout the game software life cycle to create and foster game studios.